Pemaknaan Ritual Sadhana Vajrasattva Bagi Umat Buddha di Vihara Vajra Bumi Nusantara Tangerang Banten - Suprianto Suprianto (STABN Sriwjaya, 2023)
The main problem of this research is an unknown meaning of the sadhana vajrasattva ritual for buddhists in the Vajra Nusnusantara. The purpose of this study is to describe the rituals of sadhana vajrasattva for buddhists in the Vihara Vajra Bumi Nusantara. The study data descriptive types of qualitative research. The informer in this study was the clergy and the buddhists. The data-collection techniques used by interviews, observation, and documentation using instruments of observation guides, documentation guides, and interviews. Research data validity techniques in this research used credibility, transferability, dependability and confirmability. Data analysis data Miles and Huberman, a four-step model of data collection, data reduction, data presentation, and a deduction or verification drawing. The research was: (1) Sadhana vajrasattva could be carried out by sadhaka (people of tantra) on conditions of receiving abhiseka first. Afterward the people could learn to use the dharma tools and learn sadhana. For the people wanting to engage sadhana it was suggested that the sadhana vajrasattva which was part of the prayoga chess sadhana. Sadhana herself did not escape from the readings of mahayana's silk, mantras, visualization and practicing mudra. The practice of the vajrasattva from mantra is a satacsara incantation going around, forming the mudra vajrasattva. After that the Buddha emitted a white glow of bright light that went inside through the tiles. Sadhaka imagined the body giving off a dark aura which means destroying the karma from infinity and beyond. (2) Factors that impeach sadhana vajrasattva by external and internal. External factors such as weather disorders and internal factors such as laziness and boredom. Other factors such as busy work and inconsistency execute sadhana vajrasattva. How to overcome obstacles by removing the obstacles and keeping the vajrasattva working. (3) Contact sadhana vajrasattva as sadhana founder of bad karma. Sadhana vajrasattva asa sadhana the inviting positive energy brings prosperity, health and happiness. Tujaun exercises the sadhana vajrasattva to vie for brahmavihara.